High electrostrictive properties and energy storage performances with excellent thermal stability in Nb-doped Bi0.5Na0.5TiO3-based ceramics. Issue 37 (10th July 2019) - Wu, Yichen; Wang, Genshui; Jiao, Zheng; Fan, Yuzhu; Peng, Ping; Dong, Xianlin
Abstract : Lowering T d to enlarge the temperature range between T d and the maximum dielectric temperature ( T m ) proved to be an effective strategy to enhance the thermal stability strain and energy storage properties in BNT-based ceramics. Abstract : As a promising candidate material replacing Pb(ZrTi)O3 (PZT), the lead-free Bi0.5 Na0.5 TiO3 (BNT) system exhibits outstanding piezoelectric and ferroelectric properties. However, the weak thermal stability of these electric properties hampers its practical applications. In this work, we designed and prepared novel Nb-doped 0.76Bi0.5 Na0.5 TiO3 –0.24Bi0.5 K0.5 TiO3 (BNT–BKT) ceramics with superior temperature stability of electric properties. Both strain as well as discharging properties of 5% Nb-doped BNT–BKT ceramics varied less than 3% and 12.5% respectively from room temperature to 160 °C, ascribed to the enlarged gap between the depolarized temperature ( T d or T F–R ) and the maximum dielectric temperature ( T m ). In addition, we investigated the impacts of Nb doping on the phase transition, dielectric, piezoelectric and ferroelectric behaviors of BNT–BKT ceramics in detail. Temperature dependent dielectric spectrums indicated that T d decreased below room temperature with Nb modifying, revealing that the phase structure transformed from ferroelectric into ergodic relaxor. Accordingly, the maximum strain value of 0.21% and recoverable energy storage of 1.2 J cm −3 were simultaneously acquired at the critical composition of 5% Nb incorporation. Our results provide an effective means of obtaining BNT-based ceramics with simultaneously thermally stable strain and discharge properties for wide temperature actuator and capacitor applications.